Silurian Stratigraphic Sections at Kap Tyson, Ofley Ø and Kap Schuchert, Northwestern Greenland. - Norford, B. S. (Meddelelser om Grønland, 1972)
The Silurian formations of northwestern Greenland are an intricate assemblage of graptolitic rocks and limestones of varied facies deposited at the seaward edge of a carbonate platform that probably covered most of extreme northern Greenland during Silurian time. Facies changes are abrupt and the formations are in part facies equivalents of each other. The Offley Island Formation consists of biostromal and biohermal limestones and associated calcarenites and limestone conglomerates. The cores of the biostromes and bioherms are primarily formed by stromatoporoids, algae and colonial corals. The Cape Schuchert Formation predominantly is composed of slightly argillaceous calcisiltites but includes minor biostromal and biohermal limestones and related calcarenites. The graptolitic rocks are assigned to the Cape Phillips Formation and consist of calcareous shales and mudstones, cherts, argillaceous limestones and locally developed small bioherms. The term Cape Tyson Formation is considered obsolete. All the rocks exposed at the studied localities are about Late Llandovery in age but younger and older Silurian rocks may be present elsewhere in northern Greenland. Small amounts of lead and zinc mineralisation are present within the Cape Schuchert Formation at Kap Schuchert. Petroleum residues are preserved within a prominent bioherm within the Offley Island Formation at Kap Tyson. The bioherm is about 1,100 feet (350 metres) thick and has a relief of about 800 feet (250 metres) . Extensive development of biostromal and biohermal rocks may be characteristic of the seaward edge of the Silurian carbonate platform in Greenland and the Canadian Arctic Islands. The position of the edge can be traced from Greenland to east-central Ellesmere Island and probably runs southwestward through Ellesmere Island and Grinnell Peninsula to Cornwallis Island, from there westward south of Bathurst Island and Melville Island.